Photoreactivation of fungal spores in water following UV disinfection and their control using UV-based advanced oxidation processes. (1st January 2019) - Wen, Gang; Deng, Xiaoli; Wan, Qiqi; Xu, Xiangqian; Huang, Tinglin
Abstract: The occurrence of repair system in microorganisms after ultraviolet (UV)-induced damage to them evokes concern regarding the effectiveness of UV disinfection. Most studies focus on the repair of bacteria, but little research has been conducted on the repair of fungi in water. This study aimed to investigate the photoreactivation and dark repair properties of three dominant genera of fungal spores ( Trichoderma harzianum, Aspergillus niger, and Penicillium polonicum ) isolated from groundwater. UV-based advanced oxidation processes (AOPs) (including UV/peroxymonosulfate and UV/hydrogen peroxide) were used to control their photoreactivation. The results demonstrated that the three genera of fungal spores inactivated by UV (254 nm) exhibited different levels of photoreactivation under UVA (365 nm) exposure, and the photoreactivation percentage showed that T. harzianum (51.35%) ＞ A. niger (29.07%) ＞ P. polonicum (9.01%). The photoreactivation process of fungal spores was well described by the first-order model. T. harzianum had lower photoreactivation percentage but a more rapid initial photoreactivation process than E. coli . Higher UV dosages significantly decreased the photoreactivation percentage of fungal spores. However, dark repair was insignificant following UV disinfection for all the three genera of fungal spores. After treatment by UV-based AOPs, the fungal spores exhibited the same photoreactivation trend as those treated by UV alone. However, both the maximum survival ratios and photoreactivation rate constants were reduced to varying degrees. This study revealed the photoreactivation rule of dominant genera of fungi isolated from groundwater following UV treatment alone and UV-based AOPs, which is effective for controlling fungi in water. Graphical abstract: Highlights: Fungal spores exhibit lower photoreactivation percentage than E. coli. T.harzianum has the most significant photoreactivation of the three fungal spores. The first-order model fits fungal photoreactivation process quite well. The dark repair of three genera of fungal spores is insignificant. UV-based AOPs can significantly reduce photoreactivation level of fungal spores.